Health data sharing governance - the voice of European experts interviewed - Dantas, Carina; Mackiewicz, Karolina; Tageo, Valentina (Technium Social Sciences Journal, 2021)
This article presents a summary of the main conclusions from 14 interviews with European experts, towards the creation of European guidelines on data sharing governance models and best practices, within the work carried out in the DigitalHealthEurope (DHE) H2020 project on Citizen-controlled data governance and data sharing. The overall work was broad and collected different stakeholders’ opinions and visions on the theme by a large online survey, desk research and through public events, as well as a set of personal interviews, which are the specific outcome under analysis in the present article. The answers were gathered, clustered and analysed to understand the main trends, difficulties and best practices around Europe, the governance models currently in use and, in particular, how they guarantee the security and the privacy around citizens’ data in order to build and maintain trust. Also, the incentive models used to engage with citizens, considering public and private initiatives’ latest offers for consumers available on the market were studied. The key research questions underlying the process of information collection and the design of the inquiries concerned the policy and societal framework that leads to the need for citizen-centred governance models; the ways through which citizen-led data governance models, such as health cooperatives, can respond to current control challenges; lessons to be learned from data sharing initiatives that can be capitalised for health data campaigns; and finally the best practices and initiatives that may be used as reference for benchmarking, adaptation and adoption. The interviews and preliminary reports took place in 2020, accompanying the overall discussion and developments around the European Data Strategy and European Health Data Space.